Correlation of bone marrow aspiration and biopsy findings in diagnosing hematological disorders - a study of 89 cases - Parajuli, S; Tuladhar, A (Journal of Pathology of Nepal, 2014)
Background: Bone marrow examination is an important diagnostic tool to evaluate various disorders which includes both neoplastic and non- neoplastic hematological diseases. Few studies have compared the relative value of aspirate with trephine biopsy. The present study was conducted to compare the role of bone marrow aspirate and trephine biopsy to formulate an effective and rapid method for diagnosing wide spectrum of hematological diseases. Materials and Methods: This is a three year retrospective study done from July 2010 to June 2013. A total of 95 cases presented with clinical haematological disorders; of which only 89 were biopsied and the correlation done. All the smears and sections were reviewed for morphological details and findings on aspirate and biopsy and compared to each other. Results: Out of the 89 cases selected for study; bone marrow aspiration revealed diagnostic materials in 75 cases and 14 cases were inconclusive for a definite diagnosis. The diagnostic accuracy of the bone marrow aspiration cytology was 84.26%. Eighty eight cases were diagnosed on trephine biopsy of bone marrow with diagnostic accuracy of 98.87%. Conclusion: Both the aspiration cytology and trephine biopsy complement each other for evaluating any haematological disorder. Though cellular morphology is better understood in marrow aspirates and is equally effective to biopsy in diagnosing various anemias and leukemias; however it is the histopathological study of trephine biopsy that gives well preserved marrow architecture with its all cellular and stromal components. modalities including radiological, microbiological and serological tests. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10294 Journal of Pathology of Nepal (2014) Vol. 4, 534-538